1984
DOI: 10.2307/1590234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Decreased Feed Intake on Serum and Pancreatic α-Amylase of Broiler Chickens

Abstract: Removal of feed from 20-day-old broiler chicks for 24 hours caused serum and pancreatic alpha-amylase activities to increase almost twofold. A 24-hour feeding period following feed removal caused a reduction in serum alpha-amylase to basal levels and a sixfold reduction in pancreatic alpha-amylase activity. Serum alpha-amylase levels remained elevated after long-term feed restriction in adult broilers compared with levels in full-fed controls. Reduction in feed intake in chicks caused by coccidial infections a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Amylase is considered to be of poor diagnostic value in birds (Campbell 1994), and the reported values for captive rheas are higher than in the present study (ISIS 2004). In chickens, serum amylase has been related to carbohydrate metabolism and therefore might be affected by differences in recent food intake and/or parasitism (Rodeheaver and Wyatt 1984). The fact that no ALP was detectable was probably due to the breakdown of the enzyme during heat treatment of the plasma samples before they were sent to the USA for analysis, and the fact that all the enzyme activities were lower than those reported for other ratites may have been due to partial inactivation during this process.…”
Section: Discussionmentioning
confidence: 96%
“…Amylase is considered to be of poor diagnostic value in birds (Campbell 1994), and the reported values for captive rheas are higher than in the present study (ISIS 2004). In chickens, serum amylase has been related to carbohydrate metabolism and therefore might be affected by differences in recent food intake and/or parasitism (Rodeheaver and Wyatt 1984). The fact that no ALP was detectable was probably due to the breakdown of the enzyme during heat treatment of the plasma samples before they were sent to the USA for analysis, and the fact that all the enzyme activities were lower than those reported for other ratites may have been due to partial inactivation during this process.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, pancreatic alpha amylase activity is increased in broiler chickens fasted for 24 hours (Rodeheaver and Wyatt, 1984). Re-feeding after fasting is associated with elevated digestive efficiency with increased intestine weight and duodenal maltase but no change in intestinal IgA (Fassbinder-Orth and Karasov, 2006).…”
Section: Nutritional Influences On Gastro-intestinal Functioningmentioning
confidence: 99%
“…While elevated amylase is generally considered to be indicative of pancreatic necrosis, 39 amylase also increases with acute food deprivation in chickens. 40 Increased urea is indicative of dehydration 41 and/or protein catabolism and not necessarily kidney failure. 42 The authors mention that the cholesterol of shearwaters was higher and calcium lower than observed in other seabird species and attributed this to plastic.…”
Section: Context?mentioning
confidence: 99%